Analisis Resepsi Netizen Muslim Indonesia dalam Serangan Umum #JulidFiSabilillah di Telegram - Ahmad Syafiq; Agus Saifuddin Amin (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Production is a fundamental component of economic activity that plays a strategic This study aims to analyze the reception of Indonesian Muslim netizens toward the movement on Telegram using Stuart Hall’s reception analysis theory, as well as the factors influencing their perception in responding to Zionist Israeli attacks. The research employs a qualitative approach with audience reception analysis to understand how netizens interpret the messages they receive. Data was collected through interviews with five Indonesian Muslim netizens actively involved in this campaign. The findings indicate that the campaign is effective in mobilizing the digital solidarity of Indonesian Muslims in countering hate speech against Zionist Israel. The campaign has also been predominantly received with enthusiasm by netizens, influenced by two factors: internal and external. Internal factors such as educational background, religious understanding, personal experiences, and individual values shape how netizens interpret the campaign’s messages, while external factors include community influence, social pressure, the flow of information through social media, and the socio-political relations between Indonesia and Palestine.